2017
DOI: 10.1111/tpj.13405
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐tuned regulation of the K+/H+ antiporter KEA3 is required to optimize photosynthesis during induction

Abstract: KEA3 is a thylakoid membrane localized K /H antiporter that regulates photosynthesis by modulating two components of proton motive force (pmf), the proton gradient (∆pH) and the electric potential (∆ψ). We identified a mutant allele of KEA3, disturbed proton gradient regulation (dpgr) based on its reduced non-photochemical quenching (NPQ) in artificial (CO -free with low O ) air. This phenotype was enhanced in the mutant backgrounds of PSI cyclic electron transport (pgr5 and crr2-1). In ambient air, reduced NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 39 publications
(67 reference statements)
5
78
0
Order By: Relevance
“…Experiments using overexpressing KEA3 variants with modified C-terminus demonstrated that KEA3 activity is regulated by the C-terminus harboring the KTN domain (Armbruster et al 2016). While topology experiments in the same study revealed that the C-terminus faces the lumen, experiments reported by Wang et al (2017) suggest its exposure to the stroma, where it could sense changes in NADPH levels. Although this later topology makes more sense from the point of KEA3 activity regulation, further experimental clarification is required.…”
Section: Ion Transportersmentioning
confidence: 91%
“…Experiments using overexpressing KEA3 variants with modified C-terminus demonstrated that KEA3 activity is regulated by the C-terminus harboring the KTN domain (Armbruster et al 2016). While topology experiments in the same study revealed that the C-terminus faces the lumen, experiments reported by Wang et al (2017) suggest its exposure to the stroma, where it could sense changes in NADPH levels. Although this later topology makes more sense from the point of KEA3 activity regulation, further experimental clarification is required.…”
Section: Ion Transportersmentioning
confidence: 91%
“…The strong mutant allele of pgr5 used in the previous studies is called pgr5-1 here to distinguish it from the weak allele pgr5-2 also used in this study. The pgr5-2 mutant was identified as a high-chlorophyll-fluorescence mutant in CO 2 -free air containing 5% (v/v) oxygen at 50 mmol photons m 22 s 21 (Wang et al, 2017). We characterized both alleles of pgr5 defective in the main CET pathway to assess the contribution of PGR5/ PGRL1-dependent CET to PSI photoprotection under fluctuating light intensity.…”
Section: Combining Pgr1 and Pgr5 Mutations Did Not Affect Plant Growtmentioning
confidence: 99%
“…Fully expanded leaves were used for experiments. pgr5-2 was isolated from an Arabidopsis M2 generation mutagenized by ethylmethane sulfonate by its higher chlorophyll fluorescence in CO 2 -free air containing 5% oxygen in an N 2 background (Wang et al, 2017). The pgr5-2 allele was identified by map-based cloning.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…As elucidated in Figure 1, it has been proposed that KEA3 substitutes Dc for ΔpH via antiporting H 1 with K 1 , which is required for optimization of photosynthesis during the induction of photosynthesis and in fluctuating light environments via rapidly relaxing ΔpH-dependent downregulation (Armbruster et al, 2014;Wang et al, 2017). We have identified a dominant mutant allele of KEA3, disturbed proton gradient regulation (dpgr), which harbors a point mutation in the 11th transmembrane domain and shows a phenotype Figure 1.…”
mentioning
confidence: 99%